Postmodern Çağda Müslüman Tüketicilerin Gösterişçi Tüketim Davranışları Üzerine Mukayeseli Bir Çalışma / A Comparative Study on Conspicuous Consumption Behavior of muslim Consumers in the Postmodern Era - Terzi, Hasan (Journal of History Culture and Art Research, 2016)
A Comparative Study on Conspicuous Consumption Behavior of muslim Consumers in the Postmodern Era Abstract In traditional consumer behavior literature the purpose of consumption is explained as “the activities to meet the needs” and it is assumed that decisions of consumers based on benefit-cost analysis. But today objects are consumed not only for their utilitarian values but also for carrying some meanings. Nowadays consumers use objects to demonstrate the person that they want to be. Researchers explained that the purchase and consumption of goods can be self-enhancing in two ways. First, the self-concept of an individual will be sustained and buoyed if he believes the good he has purchased is recognized publicly and classified in a manner that supports and matches his self-concept. Second, goods as symbols serve the individual, becoming means to cause desired reactions from other individuals. Today consumption has been more important for individuals and the meaning of consumption has differentiated compared to past. Therefore the conspicuous consumption behavior of Muslim consumers has been investigated. This study has been carried out with 403 Muslim people from Turkey and Indonesia. The data has been collected by face-to-face surveys and analyzed statistically. Findings of the study indicates that there are significant differences in respect to conspicuous consumption among people with the same religion. Nationality, income level and gender seem to be the major discriminating factors between the groups. Postmodern Çağda Müslüman Tüketicilerin Gösterişçi Tüketim Davranışları Üzerine Mukayeseli Bir Çalışma Öz Geleneksel tüketici davranışları yazınında tüketimin amacı ihtiyaç karşılamaya yönelik faaliyetler olarak ifade edilmekte ve tüketicinin, kararlarını fayda-maliyet analizi temeline dayandırdığı varsayılmaktadır. Ancak günümüzde tüketim objeleri doğrudan faydacı bir kullanımı olan, basit bir maddi nesne olmaktan çıkmış, bir anlam ileten, o sırada tüketicinin kim olmayı amaçladığını sergilemek için kullandığı nesneler haline gelmiştir. Önceki bazı çalışmalara göre benliğin satın alma ve tüketim yoluyla inşası iki şekilde olmaktadır. Bunlardan birincisi satın alınan ürünün toplum tarafından tanınan ve bireyin kişiliği ile örtüşüp bu kişiliği destekler nitelikte olması, diğeri başkalarının kişinin arzu etmiş olduğu tepkileri vermesi olarak tanımlanmaktadır. Tüketimin oldukça önemli hale geldiği ve taşıdığı anlamın farklılaştığı günümüz postmodern yapısı çerçevesinde Müslüman bireylerin gösterişçi özellikler sergileyip sergilemedikleri araştırılmıştır. Bu kapsamda Türkiye ve Endonezya’dan toplam 403 katılımcı ile yüz yüze anket gerçekleştirilmiş ve elde edilen veriler istatistiksel olarak analiz edilmiştir. Araştırma bulgularına göre aynı dine sahip tüketiciler arasında dahi gösteriş tüketimi açısından farklılıkların bulunduğuna işaret etmektedir. Bu farklılığın kaynakları arasında milliyet, gelir ve cinsiyet en önemlileridir.